Identification of adulteration in 11 fresh meat products by DNA mini-barcoding methods based on cytochrome C oxidase subunit Ⅰ (COⅠ) sequence - LI Jiong; WU Qiong; HU Mingjie; JIN Mengna; QIU Hongyu (浙江大学学报. 农业与生命科学版)
DNA min-barcoding methods based on cytochrome C oxidase subunitⅠ (COⅠ) sequence were developed to detect adulteration in 11 fresh meat products. DNA extraction was carried out with the DNeasy blood and tissue kit after samples were treated with vacuum freeze drying. The amplification of mini-barcoding region from DNA extracts was carried out using universal primer sets. Polymerase chain reaction (PCR) products were purified with DNA purification kit and analyzed by clone sequencing. The sequencing results were queried in GenBank (http://blast.ncbi.nlm.nih.gov/Blast.cgi) using the Blast align. The primer set COⅠ-A was found to be optimal, showing 100% amplification efficiency in 11 fresh meats (including pork, beef, mutton, chicken, duck, pigeon meat, horseflesh, ass meat, goose, rabbit meat and rat meat) with optimized PCR procedure. Eighteen meat adulteration models were founded to test the minimum detected adulteration rate by low economic value meat, and the results showed that the minimum detected adulteration rates of beef and mutton were 5%, and the rates of pigeon meat, goose, and rabbit meat were 10%, when added by the six low economic value meats (including pork, chicken, duck, horseflesh, ass meat and rat meat). To sum up, the method is simple, sensitive and reproducible, which is suitable for the detection of adulteration in the 11 fresh meat products.